Hotel Paintings and the Nature of Art: Everyday Artistic Phenomena and Methodology. (2nd January 2018) - Zangwill, Nick
Abstract: I argue that there is a problem for a wide class of theories of art that arises from counterexamples drawn from everyday artistic activity, rather than high artworld artistic activity. I explore how the counterexample functions. Part of the point is to reflect on methodological issues concerning the use of examples when considering theories of art. We will also see why thinking about everyday cases is theoretically significant.